Pandangan Hukum Nasional Dan Internasional Terhadap Organisasi Papua Merdeka: Kriminal Atau Belligerent? - Nuraini, Paundri Sekar; Anditya, Ariesta Wibisono; Pengleang, RE (Tirtayasa Journal of International Law, 2023)
Humanitarian Law develops and shifts from meaning to protect wars interpreted as wars between states, eventually developing also to protect conflicts other than the meaning of war between states. This journal was created to provide national and international law views on the Free Papua Organisation case study. The 1945 Constitution, the Declaration of Human Rights, and other regulations relevant to the research are the references for this journal study. The Free Papua Organisation is a movement whose actions will be examined based on the reference regulations. The method used in this research is the normative research method. The data collection method is done employing a literature study. The actions carried out by the Free Papua Organisation are a category of spreading violence that makes this organisation not be said to be belligerent and is more interpreted as a criminal offender.Keywords: Separatism; Free Papua Organization; National Law; International Law.